PELANGGARAN HAK ASASI MANUSIA DALAM KASUS KEKERASAN SEKSUAL TERHADAP ANAK DI LEMBAGA PENDIDIKAN KEAGAMAAN - Saidatul Aulia; Eko Handoyo (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
The rise in cases of sexual violence within religious educational institutions, which undermine students' sense of security, underscores this research. These operational issues trigger prolonged psychological trauma, the deprivation of dignity, profound fear, and obstacles to children's sustainable growth and development. The primary focus of this scientific study is to analyze forms of human rights violations and formulate a draft strategy for strengthening child protection systems in religious educational institutions. This qualitative research, conducted using a literature review, was conducted through a review of 19 draft scientific articles published between 2020 and 2025. Data collection and processing procedures were executed using structured content analysis techniques. Theoretically, the research findings reveal that sexual violence against children is a form of human rights violation that deprives victims of their right to education, a sense of security, and the physical and mental safety of their children. This violence is triggered by unequal power relations among leaders, a widespread culture of silence, and a weak internal institutional oversight system. The main conclusion emphasizes that strengthening child protection requires the implementation of effective legal regulations, the drafting of operational standards for institutional prevention, increasing safety literacy, and the provision of integrated trauma support and recovery services to create a friendly, inclusive, and conducive learning environment for all students. ABSTRAK Maraknya kasus kekerasan seksual di lingkungan institusi pendidikan keagamaan yang merenggut rasa aman peserta didik melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu timbulnya trauma psikologis berkepanjangan, perampasan harkat martabat, ketakutan mendalam, serta hambatan terhadap proses tumbuh kembang anak secara berkelanjutan. Fokus utama kajian ilmiah ini adalah menganalisis bentuk pelanggaran hak asasi manusia serta merumuskan draf strategi penguatan sistem perlindungan anak pada lembaga pendidikan keagamaan. Langkah-langkah penelitian kualitatif dengan jenis studi kepustakaan (literature review) ini dioperasikan melalui penelusuran 19 draf artikel ilmiah terbitan tahun 2020 hingga 2025. Prosedur pengumpulan dan pengolahan data dieksekusi memakai teknik analisis isi (content analysis) secara terstruktur. Temuan riset secara teoretis menyingkap bahwa kekerasan seksual terhadap anak merupakan bentuk pelanggaran hak asasi manusia yang merampas hak atas pendidikan, rasa aman, dan keselamatan fisik maupun mental korban. Terjadinya kekerasan tersebut dipicu oleh ketimpangan relasi kuasa pimpinan, maraknya budaya diam (silence culture), serta lemahnya sistem pengawasan internal institusi. Simpulan utama menegaskan bahwa penguatan perlindungan anak membutuhkan implementasi regulasi hukum yang efektif, pembuatan draf standar operasional pencegahan kelembagaan, peningkatan literasi keselamatan, serta penyediaan layanan pendampingan dan pemulihan trauma secara terpadu demi mewujudkan lingkungan belajar yang ramah, inklusif, dan kondusif bagi seluruh peserta didik.